Analisis Pengendalian Kualitas Untuk Menurunkan Jumlah Defect Produk Handle Comp 2DP Dengan Metode DMAIC Di PT. CNC - Prasmoro, Alloysius Vendhi; Indrawan, Muhammad Ade; Solihin, Solihin; Dharmayanti4, Indrani (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
PT.CNC experienced quality problems in its Handle Comp 2DP product with a current defect percentage of 4.2% where the defect tolerance target is 2.0%. The purpose of this study was to identify the causes of defects in the Handle Comp 2DP product and to provide suggestions for improving the quality control of the Handle Comp 2DP product with a tight stay mirror problem. In this study the method used is Six Sigma.. Factors that cause defects in Handle Comp 2DP are influenced by angle shifts of 11.3 ° ± 3 which are not detected on the inspection. After the sigma calculation, the sigma value before the repair was 3.2 and after the repair was made it became 3.9. Attempts to reduce the Handle Comp 2DP problem, the stay mirror problem is tight by doing a number of things repair among the process jigs plus blocks and made exactly the same as the tools in the process check finish good, added clamp toggle in position upper body racket handle cover 2 and 3 so it doesn't slide when assy process and make tool poka yoke to cover the 11.3°±3.